Oral Health Among the Elderly: A Cross Sectional study of the PERSIAN Guilan Cohort - Maryam Rabiei; Amir Ghaderi; Saba Masoudirad; Saman Maroufizadeh; Mehrnaz Asgharnezhad; Mohammadreza Naghipour; Farahnaz Joukar; Fariborz Mansour-Ghanaei (BMC Oral Health)
Abstract Introduction The oral health of the elderly is a critical component of overall health and well-being, yet it remains an underexplored area, particularly in developing countries. This study aims to assess the oral health among the elderly in the Prospective Epidemiological Research Studies of the Iranian Adults (PERSIAN) Guilan Cohort Study (PGCS) population. Methods A cross-sectional study was conducted within the PGCS, involving 1985 elderly participants. Data collection included oral examinations to determine the DMFT (Decayed, Missing, Filled Teeth) index and an assessment of oral hygiene practices. Demographic, and clinical characteristics were recorded. The data was analyzed using SPSS version 16, and GraphPad Prism version 8.1.0 software, and a significance level of 0.05 was considered. Results The mean age of the participants was 65.05 ± 3.07 years, with a higher proportion of females (53.9%). The average DMFT index was 19.87 ± 9.32. The multivariate linear regression analysis identified several significant predictors of DMFT index, including gender, marital status, education, employment status, socioeconomic status (SES), body mass index (BMI), cigarette smoking, alcohol use, tooth brushing frequency, and the use of dental floss (P < 0.05). 42.2% of the variance in the DMFT index influenced by demographic and clinical characteristics. Conclusion The study highlights the significant impact of age, gender, education, employment, physical activity, substance use, and oral hygiene practices on the oral health of the elderly in the PGCS population, underscoring the urgent need for targeted public health interventions to address modifiable risk factors and improve geriatric oral care in aging societies.